2013
DOI: 10.1051/0004-6361/201220453
|View full text |Cite
|
Sign up to set email alerts
|

The NGC 1614 interacting galaxy

Abstract: Minor mergers frequently occur between giant and gas-rich low-mass galaxies and can provide significant amounts of interstellar matter to refuel star formation and power active galactic nuclei (AGN) in the giant systems. Major starbursts and/or AGN result when fresh gas is transported and compressed in the central regions of the giant galaxy. This is the situation in the starburst minor merger NGC 1614, whose molecular medium we explore at half-arcsecond angular resolution through our observations of 12 CO (2−… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(71 citation statements)
references
References 63 publications
9
62
0
Order By: Relevance
“…König et al (2016) The red cross indicates the nucleus thatis detected in Pa α and radio continuum emission (Olsson et al 2010;Herrero-Illana et al 2014). The red circle indicates the approximate outer edge of the starburst ring (König et al 2013;Herrero-Illana et al 2014;Xu et al 2015;S16a). observation has a quasar as the flux calibrator, so we estimate the absolute systematic error on the flux calibration for our Band3 data by using the ALMA Calibrator Source Catalog.…”
Section: Band3 Data: Atacama Compact Array and 12m Arraymentioning
confidence: 99%
See 2 more Smart Citations
“…König et al (2016) The red cross indicates the nucleus thatis detected in Pa α and radio continuum emission (Olsson et al 2010;Herrero-Illana et al 2014). The red circle indicates the approximate outer edge of the starburst ring (König et al 2013;Herrero-Illana et al 2014;Xu et al 2015;S16a). observation has a quasar as the flux calibrator, so we estimate the absolute systematic error on the flux calibration for our Band3 data by using the ALMA Calibrator Source Catalog.…”
Section: Band3 Data: Atacama Compact Array and 12m Arraymentioning
confidence: 99%
“…The CO(1-0) outflow shows an extended blueshifted . The white circle indicates the approximate outer edge of the starburst ring (König et al 2013;Herrero-Illana et al 2014;Xu et al 2015;Saito 2016a). …”
Section: Aca+12m Combined Co(1-0) Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular gas in this source, imaged by the OVRO, SMA, CARMA, and ALMA interferometers, is distributed in a nuclear disk and a fainter extension (Wilson et al 2008;Olsson et al 2010;König et al 2013;Sliwa et al 2014;Xu et al 2015;Usero et al, in prep.). The recent 0.…”
Section: Ngc 1614mentioning
confidence: 99%
“…The central kpc of NGC 1614 contains a compact nucleus (45-80 pc), which dominates the near-IR continuum emission, and a bright circumnuclear SF ring (diameter∼ 600 pc), which is predominant in Paα (Alonso-Herrero et al 2001) and other SF indicators like the polycyclic aromatic hydrocarbon (PAH) emission (Díaz-Santos et al 2008;Väisänen et al 2012), cold molecular gas (König et al 2013;Sliwa et al 2014;Xu et al 2015), and radio continuum (Olsson et al 2010;Herrero-Illana et al 2014). In addition, García-Burillo et al (2015) found a massive cold molecular gas outflow (3×10 7 M ;Ṁout ∼40 M yr −1 ) which can be powered by the SF in the ring.…”
Section: Introductionmentioning
confidence: 99%